2019
DOI: 10.1111/1742-6723.13256
|View full text |Cite
|
Sign up to set email alerts
|

Homeless status documentation at a metropolitan hospital emergency department

Abstract: Objective: This study compared the prevalence of homelessness in consecutive patients presenting to a metropolitan hospital ED measured via a prospective housing screen with the prevalence of homelessness determined via retrospective audit of hospital data. Factors that altered the odds of patients being homeless and service outcomes that differed were examined for screened patients. Methods: All patients presenting to the ED during a 7 day period in 2017 were invited to complete a housing screen. A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 26 publications
(56 reference statements)
1
44
0
Order By: Relevance
“…The item usual living arrangements was one the most discordant item, particularly for patients who reside in a private residence. A previous report also which found issues with the accuracy of the coding of this VEMD item, and found homelessness was underreported in the VEMD . Researchers and policy makers need to be aware that this VEMD item may not be accurate in its current form, but can be used to identify patients who reside at home with excellent accuracy by combining the two private residency codes.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The item usual living arrangements was one the most discordant item, particularly for patients who reside in a private residence. A previous report also which found issues with the accuracy of the coding of this VEMD item, and found homelessness was underreported in the VEMD . Researchers and policy makers need to be aware that this VEMD item may not be accurate in its current form, but can be used to identify patients who reside at home with excellent accuracy by combining the two private residency codes.…”
Section: Discussionmentioning
confidence: 90%
“…Examples of recent published studies using the VEMD data include: exploring trends in ED presentations; examining the impact of major events and public awareness campaigns; and examining ED readmission rates . However, to date there is limited published research describing the accuracy of the VEMD data, and only one study was found that used the medical record as the ‘reference standard’ …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most existing healthcare systems are poor at identifying homeless patients and underestimate the prevalence of homelessness in the ED. 5 Underrecognition is exacerbated in emergency settings where homelessness is frequently perceived to be synonymous with 'rough sleeping', despite rough sleepers accounting for only 7% of Australia's homeless population. 1 In the midst of a global pandemic, the urgency to identify people who are homeless is magnified, both because homelessness poses inherent risks that exacerbate potential exposure to infection, but also because there are widespread implications for public health, including community transmission, contact tracing and the provision of isolation and quarantine services.…”
Section: Identificationmentioning
confidence: 99%